DARI TRADISIONAL KE MODERN: K.H. HIDAYAT RUHIYAT SIRODJ DAN PESANTREN ALBIDAYAH TAHUN 1971-2011 - Ratna Isnaeni Tesdy; Wawan Darmawan; Ayi Budi Santosa (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2018)
This study aimed to elaborate on the influence of Kiai Haji Yayat Ruhiyat Sirodj leadership to boarding school’s education development. Albidayah Boarding School is a modern boarding school which still maintain traditional elements. Albidayah Boarding School’s development cannot be apart from one of the figures that once led, namely Kiai Haji Yayat Ruhiyat Sirodj. The main problem in this research is “how was the education system of Albidayah Boarding School under the leadership of Kiai Haji Yayat Ruhiyat Sirodj in 1971-2011?”. This problem was examined by using a historical method that includes heuristic, critics, interpretation, and historiography. For data collection and research sources, conducted with literature study and history's witness interviews. Results study showed that under the leadership of Kiai Haji Yayat Ruhiyat Sirodj, Albidayah Boarding School has a significant development in the education field. Began with the traditional Islamic boarding school education (salafi) and developed into a modern boarding school (khalafi) by combining religion and general knowledge. The changing in the education system in Kiai Haji Yayat Ruhiyat Sirodj leadership era was made Albidayah Boarding School as official education institution under the government to build SP-IAIN (Sekolah Persiapan-Institut Agama Islam Negeri/ School Preparation-the State of Islamic Institute) in 1971. Then in 1993, Madrasah Aliyah (MA) Albidayah was built and in 2006 an Integrated Madrasah Tsanawiyah (MTs) Albidayah was also built. The curriculum that used by Albidayah Boarding School is an integrated curriculum that covers Boarding School Curriculum, the Ministry of Education and Culture Curriculum, and the Ministry of Religion Curriculum.